Autoimmune hepatitis induced by the prolonged hepatitis a virus infection - (:unkn) unknown (MEXICAN ASSOC HEPATOLOGY, 2008)
Hepatitis A virus (HAV) is the most common cause of acute viral hepatitis in the world. Rarely, acute infection may persist for a long time. Autoimmune hepatitis (AIH) may provide anti-HAV IgM positivity detection for a prolonged time. On the other hand, HAV as an infectious agent may also trigger AIH. Here we presented a case which seemed like a simple acute viral hepatitis A infection at the beginning but turned out to be an AIH according to the International Autoimmune Hepatitis Group's system. A 21-year-old female was diagnosed as symptomatic acute HAV infection with anti-HAV IgM positivity and elevated aminotransferase levels. The other viral serological tests were negative. On the 6(th), 12(th) and 18(th) months of the follow up, her anti-HAV IgM positivity still continued and transaminase levels were also 3 to 7 times high of the upper limit of normal. In addition, antinuclear antibody was positive. However, on the 19(th) month anti-HAV IgM could be detected as negative. Liver histology was prominent. The patient had a score of 16 according to the International Autoimmune Hepatitis Group's system. She was given prednisolone (10 mg/day) and azathioprine (100 mg/day). The aminotransferase levels were detected within normal ranges at the end of the first month of therapy. She was in remission during follow up for 6 years. In conclusion, prolonged HAV infection and AIH may not only trigger each other but also deteriorate the liver histology. AIH should be investigated in cases of long-lasting HAV infection in order to begin the treatment earlier. On the other hand, AIH patients should also be vaccinated for both HBV and HAV to avoid more severe diseases.
Keywords: autoimmune hepatitis; hepatitis A; chronic infection; prolonged infection; IDENTIFICATION; CHILDREN; TRIGGER